ANALISIS AKUNTANBILITAS PENGELOLAAN ALOKASI DANA DESA: Studi di Desa Tanjung Aur Kecamatan Tanjung Kemuning Kabupaten Kaur - Hernowo Noviyanto; Enlye Mariza (Gapenas Publisher, 2022)
This research aims to analyze the accountability of village fund allocation management in tanjung aur village of Tanjung Kemuning subdistrict. Because in the management there is still a lack of knowledge of the village apparatus for proper regulation. This research is included in descriptive qualitative research with reference to the accountability indicators of Mahsum et al (2004: 50). This research was conducted in Tanjung Aur Village, Tanjung Kemuning Subdistrict, speakers from the Village Head, Chairman of BPD, Village Treasurer, Village Secretary and Community Leaders and Two community people. Data collection techniques are carried out with observations, interviews, documents and Field Records. Then the data is analyzed qualitatively. The results showed that add management accountability has been categorized optimally, but one indicator is an indicator of financial accountability that is still not maximal. The Subdistrict Team should not only verify the course of ADD in the Village, but it is good for the sub-district team to follow up (review) the work of the ADD implementation team, procedures and implementation have been assessed well, seen from the use of ADD intended for the development and empowerment of tanjung Aur village community